1998
DOI: 10.1175/1520-0477(1998)079<2497:tiable>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The IMADA-AVER Boundary Layer Experiment in the Mexico City Area

Abstract: A boundary layer field experiment in the Mexico City basin during the period 24 February-22 March 1997 is described. A total of six sites were instrumented. At four of the sites, 915-MHz radar wind profilers were deployed and radiosondes were released five times per day. Two of these sites also had sodars collocated with the profilers. Radiosondes were released twice per day at a fifth site to the south of the basin, and rawinsondes were flown from another location to the northeast of the city three times per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(78 citation statements)
references
References 12 publications
6
70
2
Order By: Relevance
“…170 The relationship between meteorology and O 3 differs for different episodes. [171][172][173] Air quality measurements for criteria pollutants are reported as IMECA units (Indice Metropolitano de Calidad del Aire, or Metropolitan Index of Air Quality), which are the ratio of a measured concentration to the air quality standard for each pollutant. A contingency program is triggered when the IMECA value exceeds a certain threshold, currently 240 IMECA, or ϳ280 ppb of O 3 .…”
Section: Mexico City Metropolitan Area Mexicomentioning
confidence: 99%
“…170 The relationship between meteorology and O 3 differs for different episodes. [171][172][173] Air quality measurements for criteria pollutants are reported as IMECA units (Indice Metropolitano de Calidad del Aire, or Metropolitan Index of Air Quality), which are the ratio of a measured concentration to the air quality standard for each pollutant. A contingency program is triggered when the IMECA value exceeds a certain threshold, currently 240 IMECA, or ϳ280 ppb of O 3 .…”
Section: Mexico City Metropolitan Area Mexicomentioning
confidence: 99%
“…5 The climate is generally dry and temperate in this elevated Spatial Differences in Outdoor PM 10 Mass and Aerosol Composition in Mexico City air basin, with frequent and intense thunderstorms from June through October. Detailed meteorological characteristics during the study period are reported by Doran et al 3 Ten long-term PM 10 monitoring sites are operated by the Red Automática de Monitoreo Atmosférico (RAMA) to represent population exposure. As shown in Figure 1, six of these RAMA core sites were supplemented with 21 satellite sites and four urban/regional-scale boundary sites to better understand how well the core sites represent the outdoor exposure of their surrounding population.…”
Section: Aerosol Measurementsmentioning
confidence: 99%
“…The front Teflon-membrane filter was used to measure mass by gravimetry, light absorption (b abs ) by densitometry, and 40 elements (Na, Mg, Al, Si, P, S, Cl, K, Ca, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, As, Se, Br, Rb, Sr, Y, Zr, Mo, Pd, Ag, Cd, In, Sn, Sb, Ba, La, Au, Hg, Tl, Pb, and U) by X-ray fluorescence (XRF), 9 and the backup citric acid-impregnated cellulose-fiber filter was used to measure gaseous NH 3 by automated colorimetry. On a parallel unit, the front quartz-fiber filter was used to measure water-soluble ions (Na + and K + by atomic absorption spectrometry; 10 Cl -, non-volatilized NO 3 -, and SO 4 2-by ion chromatography 11 ) and carbon [organic carbon (OC) and elemental carbon (EC) by the IMPROVE thermal evolution ], and the backup NaCl-impregnated cellulosefiber filter was used to measure volatilized NO 3 -by ion chromatography. All of the sampling sites used the Teflon/ citric acid filter pack configuration, and about half of the sites used both configurations sampling side by side.…”
Section: Aerosol Measurementsmentioning
confidence: 99%
See 2 more Smart Citations